BOND-STRETCH ISOMERISM AND THE FULLERENES - Austin, S; Baker, J; Fowler, P; Manolopoulos, D (1994)
It is argued that because many fullerene molecular graphs admit multiple totally symmetric Kekulé structures, the fullerene class of molecules may provide examples of bond-stretch isomerism (π-tautomerism). Calculations on the prototype D2 isomer of C28 demonstrate the existence on the potential surface for 28 carbon atoms of at least three enantiomorphic pairs of fullerene minima of this symmetry, all with the same connectivity. The three patterns of long and short bonds in these isomers are 'orthogonal' in that any one CC bond is formally double in precisely one and formally single in precisely two of the structures.